Retrosynthetic Simplicity - Levin, Mark D. (Synlett, 2023)
Retrosynthetic simplicity is introduced as a metric by which methods can be evaluated. An argument in favor of reactions which are retrosynthetically simple is put forward, and recent examples in the context of skeletal editing from my own laboratory as well as contributions from others are analyzed critically through this lens.1 Introduction2 Example 1: Quinoline to Quinazoline (One Product, Two Starting Materials)3 Example 2: Benzene to Pyridine (Two Products, One Starting Material)4 Caveats, Counterarguments, and Conclusions
Keywords: skeletal editing; retrosynthesis; simplicity; heterocycles; methodology